2021
DOI: 10.1371/journal.ppat.1009420
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-specific clinical and immunological features of coronavirus disease 2019

Abstract: To simultaneously determine clinical and immunological responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in young and old females and males, 681 coronavirus disease 2019 (COVID-19) patients and 369 normal controls (NCs) were analyzed based on age and sex classifications using multiple linear regression analysis. Compared to the age-matched NCs, both young and old male and female non-comorbid COVID-19 patients had lower lymphocyte counts and alanine aminotransferase (ALT) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Post-mortem analysis using optical imaging and DPA-713-IRDye680LT confirmed these findings. Additionally, multicolor flow cytometry demonstrated that the lungs of male hamsters had a higher percentage of CD11b + myeloid cells (macrophages, phagocytes) versus females, but higher lymphocyte infiltration was detected in females, which is consistent with human studies [ 39 , 48 ]. Given the limited availability of reagents, a more detailed flow cytometric analysis could not be performed.…”
Section: Discussionsupporting
confidence: 87%
“…Post-mortem analysis using optical imaging and DPA-713-IRDye680LT confirmed these findings. Additionally, multicolor flow cytometry demonstrated that the lungs of male hamsters had a higher percentage of CD11b + myeloid cells (macrophages, phagocytes) versus females, but higher lymphocyte infiltration was detected in females, which is consistent with human studies [ 39 , 48 ]. Given the limited availability of reagents, a more detailed flow cytometric analysis could not be performed.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, there are different opinions and discussions about the e cacy and e ciency of immunizations with anti-SARS-CoV-2 vaccines in relation to the potential for generating protective immunity and the persistence of immunological memory [9,21], especially with regard to variables such as sex and age. In general, the immune response exhibits distinct dynamics based on factors such as sex [11,22] and immune system senescence [12]. In the present study, the frequency of anti-SARS-CoV-2 total antibodies was signi cantly higher in females, which corroborates the literature describing females as presenting increased in ammatory and humoral responses to COVID-19 [12].…”
Section: Discussionsupporting
confidence: 90%
“…A recent meta-analysis study showed that the Coronavac vaccine would be e cient in generating neutralizing antibodies (Rogliani et al, 2021), which together with the present results, particularly those obtained for anti-SARS- Considering that the immune response may have distinct dynamics supported by factors related to sexual dimorphism (Ulhaq et al, 2020;Jin et al 2021) and physiological senescence of the immune system (Ciarambino et al, 2021), the frequency of anti-SARS-CoV-2 total antibodies observed in the present study was signi cantly more frequent in females, which corroborates the literature describing females, when compared to males, as presenting increased in ammatory and humoral responses in response to COVID-19 (Ciarambino et al, 2021).…”
Section: Discussionsupporting
confidence: 81%